Identification of A-Type Proanthocyanidins in Cranberry-Based Foods and Dietary Supplements by Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry, First Action Method: 2019.05. (10th August 2020) - Esquivel-Alvarado, Daniel; Alfaro-Viquez, Emilia; Krueger, Christian G; Vestling, Martha M; Reed, Jess D
Abstract: Background: Cranberry proanthocyanidins (c-PAC) are oligomeric structures of flavan-3-ol units, which possess A-type interflavan bonds. c-PAC differs from other botanical sources because other PAC mostly have B-type interflavan bonds. Cranberry products used to alleviate and prevent urinary tract infections may suffer from adulteration, where c-PAC are replaced with less expensive botanical sources of PAC that contain B-type interflavan bonds. Objective: Identifying the presence of A-type interflavan bonds in cranberry fruit and dietary supplements. Methods: Thirty-five samples reported to contain A-type PAC (cranberry fruit and cranberry products) and 36 samples reported to contain B-type PAC (other botanical sources) were identified and differentiated using MALDI-TOF MS, deconvolution of overlapping isotope patterns, and principal component analysis (PCA). Results: Our results show that both MALDI-TOF MS and deconvolution of overlapping isotope patterns were able to identify the presence of A-type interflavan bonds with a probability greater than 90% and a confidence of 95%. Deconvolution of MALDI-TOF MS spectra also determined the ratio of A-type to B-type interflavan bonds at each degree of polymerization in cranberry fruit and cranberry products, which is a distinguishing feature of c-PAC in comparison to other botanical sources of PAC. PCA shows clear differences based on the nature of the interflavan bonds. Conclusions: MALDI-TOF MS, deconvolution of overlapping isotope patterns of MALDI-TOF MS spectra, and PCA allow the identification, estimation, and differentiation of A-type interflavan bonds in cranberry-based foods and dietary supplements among other botanical sources containing mostly B-type interflavan bonds.